1998
DOI: 10.2981/wlb.1998.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting clutch Size and Duckling Survival in the Common Goldeneye Bucephala clangula

Abstract: Female age and condition as well as nesting schedule may affect clutch size and chick survival, which both are important factors affecting the annual reproductive output. Clutch size and chick survival are often interrelated in altricial birds but in precocial species the interrelation is dubious. To study factors affecting clutch size and the survival of ducklings in the common goldeneye Bucephala clangula, we examined ringing‐recovery data, supplied by ringers, from seven intensively studied goldeneye popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 29 publications
2
34
1
5
Order By: Relevance
“…That only ∼ 21% of females produced virtually all recruits is consistent with patterns reported for other vertebrates (Clutton‐Brock , Newton ) including several duck species (Blums and Clark ). Previous analyses of factors affecting recruitment processes in this goldeneye population had much smaller sample size of recruits (n = 31) and used statistical techniques (pair‐wise comparisons in terms of brood size, timing of nesting and female age; for details see Milonoff et al ) that could not distinguish direct and indirect effects of explanatory variables. Therefore, even though hatching date and female age both affected recruitment rate, it was not possible to assess the relative contribution of age per se to reproductive success (Milonoff et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That only ∼ 21% of females produced virtually all recruits is consistent with patterns reported for other vertebrates (Clutton‐Brock , Newton ) including several duck species (Blums and Clark ). Previous analyses of factors affecting recruitment processes in this goldeneye population had much smaller sample size of recruits (n = 31) and used statistical techniques (pair‐wise comparisons in terms of brood size, timing of nesting and female age; for details see Milonoff et al ) that could not distinguish direct and indirect effects of explanatory variables. Therefore, even though hatching date and female age both affected recruitment rate, it was not possible to assess the relative contribution of age per se to reproductive success (Milonoff et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses of factors affecting recruitment processes in this goldeneye population had much smaller sample size of recruits (n = 31) and used statistical techniques (pair‐wise comparisons in terms of brood size, timing of nesting and female age; for details see Milonoff et al ) that could not distinguish direct and indirect effects of explanatory variables. Therefore, even though hatching date and female age both affected recruitment rate, it was not possible to assess the relative contribution of age per se to reproductive success (Milonoff et al ). The path analysis results presented here were based on four times more data and revealed that female age did not directly affect offspring recruitment; rather, an age effect is mediated via indirect effects on timing of breeding, body condition and brood size.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the nest site characteristics, the occurrence of CBP was also associated with nesting schedule: early broods were more frequently parasitized than late broods. Early goldeneye broods have a higher chick survival rate and produce more recruits (Dow and Fredga 1984, Milonoff et al 1998). Furthermore, early breeding attempts often are in nest sites that have low predation risk (Pöysä 1999b).…”
Section: Discussionmentioning
confidence: 99%
“…females not born in the study area but captured as adults the first time), we used the number of nesting years (i.e. the number of years from the first recorded nesting attempt for a given female before current nesting attempt) as the measure of female experience (see also Dow and Fredga 1984, Milonoff et al 1998, 2002). As an index of female condition, we used the residuals from the body mass on wing length regression based on pooled data (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation